Analisis Layanan Transportasi Online Sebagai Pilihan Moda Transportasi Mahasiswa Universitas 17 Agustus 1945 Surabaya - Rizky Ilham Ramadhan Prayogi; Nurani Hartatik (Pusat Riset dan Inovasi Nasional, 2023)
Technological advancements will eventually have an impact on all parts of society's environment, including transportation. Based on application technology, online transportation is a means of transportation that allows its consumers to employ the services of motor vehicles or cars at any time. The study's goal is to collect data on the efficacy of online transportation services by assessing the level of efficiency of online transportation. The questionnaire distribution approach was used to reach 388 University 17 Agustus 1945 Surabaya, utilizing online transportation services. A descriptive quantitative method approach is used in this study with statistical analysis of weighting based on the level of user satisfaction. As a result of this study, the online transportation service has met the expectations of its use where in achieving its effectiveness has already been very good with a service efficiency rate of 82%, but not optimal on the pick-up point precision service. The highest level of efficiency on the safe service variable is applied to the means of transport with an efficiency rate of 84.02%, followed by the safe and easy service variables with the efficiency level value of 83.08%, while the speed variable with the effectiveness level value is 81.08%, on the cost variable charged with the efficacy level of 80.14%, and on the accuracy variable that has the efficiencies level of 77.68%.